Unconventional gas reservoirs : evaluation, appraisal, and development - Islam, M. Rafiqul (Gulf Professional Publishing, 2015)
Natural gas, especially unconventional gas, has an increasingly important role in meeting the world's energy needs. Experts estimate that it has the potential to add anywhere from 60-250% to the global proven gas reserve in the next two decades. To maintain pace with increasing global demand, Unconventional Gas Reservoirs provides the necessary bridge into the newer processes, approaches and designs to help identify these more uncommon reservoirs available and how to maximize its unconventional potential. Loaded with reservoir development and characterization strategies, this book will sho.
Keywords: Gas reservoirs.; elektronické knihy; electronic books